Change Management in the VUCA Era (Universitas Terbuka, 2023)
Advances in technology had driven globalization so that the business environment changes very quickly. If previously changes could be planned, change was uncontrollable or even unpredictable now. This condition mastered the organizations had no other choice except to change. Of course, it was not easy for organizations that preferred to stay in the safe zone. It must be realized that indeed change was not easy and required a process. This paper aimed to look at the role of change management in organizational change based on references and studies related to change management. Change was not just transfer of technology or digitaliization but changes that were followed along with changes in mindset and changes in organizational culture of all members. Couples of examples of failures in change cases because they were not being followed by change in mindset. An alternative solution that could be done is to implement change management, the way of how to manage the people affected by these changes. In other words, change management was a way of changing from resistance to change advocates.